Philippines Economic Update, June 2020 : Braving the New Normal - World Bank (World Bank, Washington, DC, 2020)
A series of unforeseen events caused an abrupt halt to the Philippines' strong growth momentum in early 2020. The Philippine economy carried its strong growth momentum from the second half of 2019 into early 2020 thanks to positive consumer confidence, robust macroeconomic fundamentals, and an improvement in the external sector. However, the eruption of Taal Volcano in early January, the spread of the Coronavirus Disease 2019 (COVID-19) outbreak in the region, and the rise of COVID-19 infection cases in the Philippines in March, forced the economy to a near halt in the latter part of March due to severe disruptions in manufacturing, agriculture, tourism and hospitality, construction, and trade. The economy contracted by 0.2 percent year-on-year in the first quarter of 2020, the first contraction in over two decades, and was a sharp reversal from the 5.7 percent growth over the same period in 2019. Leading indicators that track economic activity in real time suggest that the contraction would be even more severe in the second quarter as most regions of the country entered an enhanced community quarantine (ECQ) in mid-March.